Nutrition Education in the Prevention of Adolescent Obesity - Shafa Minda Maliran; Iriyani Kamaruddin; Ratih Wirapuspita Wisnuwardani (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : Adolescent obesity in Indonesia is increasing and poses a high risk of chronic diseases such as type 2 diabetes and cardiovascular disorders. One contributing factor is poor nutrition knowledge and unhealthy eating patterns. Objective : This study aimed to evaluate the effectiveness of nutrition education in improving adolescents’ knowledge as an effort to prevent obesity. Research Methods/ Implementation Methods : The intervention was delivered through interactive lectures, group discussions, and visual media (posters, booklets, videos), covering topics such as balanced nutrition, reducing excessive sugar and fat intake, and choosing healthy snacks. Thirty adolescent respondents participated in a pretest and posttest, with data analyzed using the Wilcoxon test and crosstab. Results : The Wilcoxon test showed a significant difference between pretest and posttest scores (p = 0.004), with all respondents achieving a good knowledge category after the intervention. However, 73.3% of respondents still demonstrated less supportive attitudes. Conclusion/Lesson Learned : In conclusion, nutrition education effectively increased nutrition knowledge, but sustainable programs focusing on behavior habituation through the involvement of schools, families, and social media are recommended to foster long-term positive attitudes.